P45 Non-invasive methods for the estimation of mpap in COPD patients using cardiac mri. (15th November 2016) - Johns, CS; Capener, D; Hammerton, C; Shotton, K; Kiely, DG; Wild, JM; Swift, AJ
Abstract : Background: Pulmonary hypertension (PH) is important in COPD as it predicts death and hospitalisation. The diagnosis is made by right heart catheter (RHC). Several predictive cardiac MRI (CMR) models have been proposed to estimate mean pulmonary artery pressure (mPAP): VMI/IVS: –4.6 + (interventricular septal angle (IVS) x 0.23) + (ventricular mass index (VMI) × 16.3) 1 PA/RV: × 21.806 + (IVS × 0.31) + (VMI × 11.5) + (Diastolic pulmonary artery (PA) area × 0.01) – (PA relative area change × 0.22) Alpha-index: minimum PA area/right ventricular ejection fraction 2 The predictive value of these models in a COPD population with suspected PH remains unknown, so we aimed to assess their diagnostic accuracy. Methods: All consecutive patients referred to a PH centre from April 2012 to October 2015 with suspected PH were assessed. Any patient with a formal diagnosis of COPD was included. Sensitivity and specificity were calculated using diagnostic cut-offs published in the literature (VMI/IVS = 32, PA/RV model = 25, alpha index = 7.2). Ethical approval was granted. Results: 1864 patients were referred to the PH centre, 145 had a documented diagnosis of COPD, 102 had MRI and RHC within 90 days. All CMR models showed good correlation with RHC measured mPAP (Pearson's R for (i) VMI/IVS = 0.689, (ii) PA/RV model = 0.732 and (iii) Alpha-index = 0.527). Sensitivity and specificity for (i) VMI/IVS were 92% and 79%, (ii) PA/RV model 80% and 93% and (iii) for Alpha index 100% and 13% respectively. An ROC curve for the diagnosis of PH for each of the models is provided. Conclusion: VMI/IVS and PA/RV models both have good accuracy in the detection of PH in COPD patients. Alpha-index had a low specificity, largely due to a low diagnostic threshold. As such these models are useful in the assessment of PH, and likely prognosis in patients with COPD. References: Swift AJ, et al . Noninvasive estimation of PA Pressure, Flow, and Resistance With CMR Imaging. JACC Cardiovasc Imaging 2013;6 (10):1036–47. Moral S, et al . New index alpha improves detection of pulmonary hypertension in comparison with other cardiac magnetic resonance indices. Int J Cardiol 2012;161 (1):25–30.